(3QjGV GdeSGFd aj JMbjb GdCMcGe HGdOdGFds - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs ((3eOjfI GdeTgOs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3cJGH GdJLGQI gj aj GddZI GdcSH haj GdTQY Ydi JYQja GdeUfa hLeGYI YbO GdeYGQVIs
(3BNQgG (B:s
(3BNQgG(B: (3hdPG bjd dG jSbW GdEQK HgPG GddYGf hEf LhRgG GdGSbGW GdMO dGSJbQGQg HGdehJ adG jQaV GddYGf GdeJLOO hGdMeO ddg SHMGfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 17s
(3GdPQjYI, L (B11: 240s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis